T Cell Receptor–Major Histocompatibility Complex Interaction Strength Defines Trafficking and CD103+ Memory Status of CD8 T Cells in the Brain - Sanecka, Anna; Yoshida, Nagisa; Kolawole, Elizabeth Motunrayo; Patel, Harshil; Evavold, Brian D.; Frickel, Eva-Maria (Frontiers in Immunology, 2018)
T cell receptor-Major histocompatibility complex (TCR-MHC) affinities span a wide range in a polyclonal T cell response, yet it is undefined how affinity shapes long-term properties of CD8 T cells during chronic infection with persistent antigen. Here, we investigate how the affinity of the TCR-MHC interaction shapes the phenotype of memory CD8 T cells in the chronically Toxoplasma gondii-infected brain. We employed CD8 T cells from three lines of transnuclear (TN) mice that harbour in their endogenous loci different T cell receptors specific for the same Toxoplasma antigenic epitope ROP7. The three TN CD8 T cell clones span a wide range of affinities to MHCI-ROP7. These three CD8 T cell clones have a distinct and fixed hierarchy in terms of effector function in response to the antigen measured as proliferation capacity, trafficking, T cell maintenance and memory formation. In particular, the T cell clone of lowest affinity does not home to the brain. The two higher affinity T cell clones show differences in establishing resident memory populations (CD103+) in the brain with the higher affinity clone persisting longer in the host during chronic infection. Transcriptional profiling of naïve and activated ROP7-specific CD8 T cells revealed that Klf2 encoding a transcription factor that is known to be a negative marker for T cell trafficking is upregulated in the activated lowest affinity ROP7 clone. Our data thus suggest that TCR-MHC affinity dictates memory CD8 T cell fate at the site of infection.